Study on Impact of Social Media Marketing of Mobile Phone Generation Z Psychology for Online Shopping in Ahmedabad - Makwana, Manthan; Jignesh, Rohit; Vidani, Jignesh (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study investigates the impact of social media marketing on the psychology of Generation Z towards mobile online shopping in Ahmedabad. The data collection method used in this study is descriptive method. Through a comprehensive analysis of twelve alternative hypotheses, the study examines the relationship between social media influence and consumer behavior. The study highlights a critical gap in understanding the nuanced psychological responses of this demographic, particularly regarding their skepticism towards social media marketing. The study emphasizes the need for further research to explore the cultural context of Ahmedabad and the unique characteristics of Generation Z, as well as the dynamics of evolving social media platforms. Insights from this study can inform mobile phone brands in developing more effective and culturally relevant marketing strategies